Cover Image, Volume 232, Number 2, February 2017. Issue 2 (February 2017) - Shami, Gerald J.; Cheng, Delfine; Braet, Filip
Abstract : Cover : The cover image, by Gerald John Shami et al., is based on the From the Bench Paper Combined Multidimensional Microscopy as a Histopathology Imaging Tool, DOI:10.1002/jcp.25470 .